Keeping up appearances : women’s experiences of economic abuse in the context of coercive control : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Psychology at Massey University, Papaioea, Manawatū, Aotearoa - Billington, Chloe R. (Massey University, 2025)
Economic abuse is a pervasive yet under-recognised form of intimate partner violence (IPV) that undermines women’s autonomy, economic security, and social participation. This study, grounded in feminist standpoint epistemology, used semi-structured interviews and Thematic Analysis to explore the lived experiences of six women in Aotearoa New Zealand who experienced economic abuse within coercively controlling heterosexual relationships, both pre and post separation. Guided by the entrapment framework and Evan Stark’s theory of coercive control, the research examined how dominant constructions of gender norms, IPV, and class shape women’s experiences. Three core themes were co-constructed: Romantic Love, Motherhood and Leaving. Romantic Love explores how heteronormative romantic scripts and gendered performance facilitate economic entrapment. Motherhood highlights how men exploit maternal identity and the direct impact of economic abuse on children. Leaving reveals how economic abuse of women and children persists post separation through manipulation of legal and financial systems. Despite these challenges, the women demonstrated agency, resistance, and active help-seeking. With limited research on economic abuse in Aotearoa New Zealand, this study aims to contribute to the growing literature and deepen understanding of the social, cultural, and political frameworks that enable men to perpetrate economic abuse through various means. While violence is sometimes a feature or tactic of coercive control, the priority focus of physical harm in the domestic violence paradigm means that the impact of persistent behaviours that are less socially censured than physical violence is significantly underestimated. IPV stems from unequal gendered power relations upheld by political, social, and cultural norms. Middle-class professional men, in particular, benefit from unchecked privilege and cultural associations that resource silence and limit recognition and support for women. Economic instability is both a precursor and outcome of economic abuse, and a barrier to leaving and post-separation survival. Currently subsumed under psychological abuse in legislation, economic abuse warrants recognition as a distinct legal construct due to its unique mechanisms and measurable financial impacts.
Keywords: 440209 Gender and crime; 440504 Gender relations